(untitled) (Innovative professional education, 2024)
The article summarizes theoretical approaches to conducting a pedagogical experiment as a method of empirical research in the system of vocational education. The expediency of the phased formation of professional competence of future motor transport mechanics in the conditions of targeted pedagogical influence is substantiated. The structure of a complex pedagogical experiment, which included preparatory, stating, formative and final stages, each of which had clearly defined tasks, methods and means of implementation, is characterized. The article presents an effective methodology for the formation of competence based on the integration of practice-oriented learning, case method, cloud technologies and psychological support. The results of the study confirm the effectiveness of the proposed pedagogical conditions and the prospects for their implementation in the educational process.